9.07.001: "Bridgett's Pub, 6 September 1991: Seamus Creagh, Don Walsh, Paddy Mackey" - Walsh, Don; Creagh, Séamus; Mackey, Paddy (1991)
Shane Kelly recorded the gig at Bridgett's Pub. There were two nights; this is the recording from 6 September 1991.